Resistência à tração diametral de cimentos de ionômero de vidro submetidos à aplicação de ondas de ultrassom - Souza, Mônica Irma Aparecida Valdeci De [UNESP] (2013)
INTRODUCTION: The glass ionomer cement is a dental material that has limitations of use due to its mechanical properties, such as low wear resistance, hardness, tensile and compressive diametral. Based on this, this study investigated the effect of ultrasonic excitation on the GIC in different application times, through the diametral tensile strength. MATERIAL AND METHOD: The materials used were Ketac Molar EasyMix (KME) and Ketac Cem EasyMix (KCE). Were made 10 specimens for each condition studied: control group, and the groups that received application of ultrasound for 15s, 30s and 45s, for both materials. The ultrasonic excitation was applied during the initial setting reaction of GIC, soon after its insertion into the silicone matrix. The values of the diametral tensile strength were analyzed by Shapiro Wilk test and ANOVA (α = 0.05). RESULT: The application of ultrasonic excitation showed no statistically significant effect on diametral tensile strength of the materials tested, regardless of the time of application (p > 0.05). The KME resistance showed statistically greater than the KCE (p = 0.023). CONCLUSION: The use of ultrasound waves did not influence the diametral tensile strength of CIV tested regardless of their time of application.